Longitudinal antigenic and seroepidemiological analyses of parechovirus A1 in Yamagata, Japan. Issue 4 (30th March 2023) - Mizuta, Katsumi; Itagaki, Tsutomu; Katsushima, Fumio; Katsushima, Yuriko; Sasaki, Mika; Komabayashi, Kenichi; Ikeda, Yoko; Aoki, Yoko; Matsuzaki, Yoko
Abstract: To investigate the antigenic changes in parechovirus 1 (PeVA1), seroepidemiological analyses were performed against the Harris strain (Harris), isolated in 1956, and PeVA1/Yamagata.JPN/2021‐4785, isolated in 2021, using immune sera and 207 and 237 human serum specimens collected in 2021 and 1976, respectively. Although rabbit immune sera showed the highest neutralization antibody (NT‐Ab) titers against the immunized viruses at 1:12 800–1:102 400, they were cross‐reactive at 1:400–1:800. All 62 Yamagata isolates obtained between 2001 and 2021 (Yamagata strains), belonging to phylogenetic lineage 1B, reacted more strongly (mostly 4–64 times) to antiserum against PeVA1/Yamagata.JPN/2021‐4785 than to antiserum against Harris, belonging to phylogenetic lineage 1 A. Human serum specimens obtained in 2021 showed higher NT‐Ab titers against PeVA1/Yamagata.JPN/2021‐4785, whereas those obtained in 1976 had similar NT‐Ab titers against both strains. These findings suggested that Yamagata strains and Harris were antigenically cross‐reactive, although there were differences. There are still high NT‐Abs titers present against Harris in 2021 in particular, indicating that PeVA1 has been in circulation with high immunity in the population. In conclusion, this study suggested that PeVA1 has been endemically perpetuated with only minor antigenic changes as well as with high immunity over several decades in the community.